2007
DOI: 10.1007/s10519-007-9166-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective Breeding of Reduced Sensorimotor Gating in Wistar Rats

Abstract: Prepulse inhibition (PPI) of startle is an operational measure of sensorimotor gating that is reduced in some neuropsychiatric disorders (e.g. schizophrenia). Animal models have revealed insight into the neuronal and pharmacological underpinnings of PPI-deficits. Recent work has shown that a PPI-deficit can be selectively bred in Wistar rats and is already stable in the second filial generation. We here report on developmental and parametric characteristics of sensorimotor gating deficits in the 4th and 6th fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…So far, invasive methods such as brain lesions, substance administration, electrical stimulation (Swerdlow et al, 2001a) and genetic approaches like selective breeding, inbred strain comparisons and mutant analysis (Swerdlow et al, 2000; Geyer et al, 2002; Schwabe et al, 2007) served to study brain circuitries regulating startle and PPI. The proposed pathway mediating PPI of acoustic startle comprises inferior and superior colliculus, pedunculopontine and laterodorsal tegmental nuclei as well as substantia nigra.…”
Section: Introductionmentioning
confidence: 99%
“…So far, invasive methods such as brain lesions, substance administration, electrical stimulation (Swerdlow et al, 2001a) and genetic approaches like selective breeding, inbred strain comparisons and mutant analysis (Swerdlow et al, 2000; Geyer et al, 2002; Schwabe et al, 2007) served to study brain circuitries regulating startle and PPI. The proposed pathway mediating PPI of acoustic startle comprises inferior and superior colliculus, pedunculopontine and laterodorsal tegmental nuclei as well as substantia nigra.…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to develop selective breeding (e.g. Logue et al 1997;McCaughran et al 1997;Schwabe et al 2007), whilst another is to compare existing, usually inbred strains with relatively stable genetic backgrounds (Bullock et al 1997;Crawley et al 1997;Paylor and Crawley 1997). The inbred DBA/2 mouse strain has attracted interests recently in its potential relevance to psychosis-related traits in comparison to another common inbred mouse strain-the C57BL/6 strain-as the reference line (Olivier et al 2001;Spielewoy and Markou 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies used the selective-breeding procedures to develop new lines (or strains) of rats in psychiatric disorders such as epilepsy, depression or schizophrenia. Schwabe et al have shown that a PPI-deficit can be selectively bred in Wistar rats and is already stable in the second filial generation [5]. Cognitive abilities also show a significant inheritance, as indicated by earlier experiments in selectively bred rats [44].…”
Section: Genetic Modelsmentioning
confidence: 93%
“…Sensory gating, as a non specific sign, is reduced in a variety of neuropsychiatric disorders (e.g. Huntingtons's disease, Tourette's syndrome, autism, bipolar or panic disorder) including schizophrenia [3][4][5].…”
Section: Symptoms Of Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation